Pemetaan Kejadian Stunting pada Balita di Kabupaten Klaten Tahun 2021 - astuti, Fera; Ningrum, Dina Nur Anggraini (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
The Klaten Regency stands as one of the districts yet to adopt a mapping system for managing stunting cases. The objective of this study was to identify the prevalence and risk factors associated with stunting among toddlers across the 26 sub-districts of Klaten Regency in 2021. Employing a cross-sectional design coupled with an ecological study and mapping approach, the research was conducted throughout 2021. The study encompassed a population of 26 sub-districts, accounting for a total of 6,949 reported cases of stunting in 2021. Total sampling was employed as the sampling technique. The findings revealed that in the mapping of correlated risk factors—specifically, variables such as low birth weight, chronic energy deficiency in pregnant women, birth length, and antenatal care coverage—four sub-districts were identified as having a high risk of stunting. For prospective researchers, it is recommended to explore additional risk factors associated with stunting, such as the prevalence of early marriages, the percentage of individuals living below the poverty line, the proportion of women attaining secondary education or higher, or by incorporating supplementary primary data sources, like the employment status of toddlers' parents.